Fodder Trees in Himachal Pradesh - Negi, S. S. (Indian Forester, 1977)
Apropos the plantation of fodder trees in Himachal Pradesh the aspects of some potential tree fodders in the State are discussed. Possibility of converting the nutritious tree leaves harvested at the right a protein-rich meals is indicated.